2015
DOI: 10.1002/2015gl066714
|View full text |Cite
|
Sign up to set email alerts
|

First simultaneous measurements of Na and K thermospheric layers along with TILs from Arecibo

Abstract: This work presents the first simultaneous observations of Na and K between 120 and 150 km altitudes along with ionospheric tidal ion layers (TILs) obtained on 30 January 2006 data from Arecibo. The latter displays an average downward phase velocity of ~14.7 ms−1. However, the neutral layers descend together at a much slower velocity of about ~0.69 ms−1. This indicates that thermospheric atomic metal layers are not necessarily associated with TILs. The ratio of the average Na/K abundances in thermosphere is ~35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 53 publications
3
35
0
Order By: Relevance
“…We thus investigate the relevant TEC variations in Figures 2d-2g and geomagnetic variations in Figures 2h-2k, respectively, during the occurrence of the reporting layers. Raizada et al (2015) not only had simultaneous observation of thermospheric Na and K thermospheric layers but also had simultaneous high-resolution observation of ionospheric electron distribution with incoherent scatter radar. Furthermore, after reviewing the Dst (disturbance storm time) index (http://wdc.kugi.kyoto-u.ac.jp/), we found that there were no geomagnetic storms in these nights.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We thus investigate the relevant TEC variations in Figures 2d-2g and geomagnetic variations in Figures 2h-2k, respectively, during the occurrence of the reporting layers. Raizada et al (2015) not only had simultaneous observation of thermospheric Na and K thermospheric layers but also had simultaneous high-resolution observation of ionospheric electron distribution with incoherent scatter radar. Furthermore, after reviewing the Dst (disturbance storm time) index (http://wdc.kugi.kyoto-u.ac.jp/), we found that there were no geomagnetic storms in these nights.…”
Section: Discussionmentioning
confidence: 99%
“…The newest discovery of thermospheric neutral metal layers extending to 130-170 km have stimulated considerable community interest in part due to their use as tracers for resonance lidar temperature and wind measurements, thus potentially tripling the altitude range for atmospheric dynamics studies into the thermosphere. While three of the five additional publications reported Na layers, Friedman et al (2013) reported K layers and Raizada et al (2015) reported simultaneous observation of Na and K layers. Since then, there are five additional publications reporting layers to beyond 130 km, one (Tsuda et al, 2015) from another Antarctic station over Syowa Station (69.0°S, 39.6°E); two (Friedman et al, 2013;Raizada et al, 2015) from the same tropic station, Arecibo (18.35°N, 66.75°W); and two from lower midlatitude stations at Lijiang, China (26.7°N, 100.0°E) by Gao et al (2015), and Cerro Pachón, Chile (30.25°S, 70.74°W) by Liu et al (2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, at low latitude, thermospheric Na layers up to 170 km with descending tidal phases at Lijiang (26.7°N, 100.0°E) are also seen [ Xue et al ., ; Gao et al ., ]. Later, Raizada et al [] compared the simultaneous observations of Na and K between 120 and 150 km altitudes along with ionospheric tidal ion layers (TILs). They found that the TILs display an average downward phase velocity of ~14.7 ms −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we report simultaneous observations of Na, K, and temperature carried out at the Arecibo Observatory (AO), which houses three resonance lidars, including a K Doppler lidar with temperature capability. Potassium and any other metal species from Na, Fe, Ca, and Ca + can be observed simultaneously [e.g., Tepley et al, 2003;Raizada et al, 2004Raizada et al, , 2011Raizada et al, , 2012Raizada et al, , 2015aRaizada et al, , 2015b. Simultaneous observation of K, Na, and temperature, however, is limited to only a few nights.…”
Section: Introductionmentioning
confidence: 99%